Product Design and Quality as Determinants of Oppo Purchase Decisions: Desain Produk dan Kualitas sebagai Faktor Penentu Keputusan Pembelian Oppo - Hidayat , Rahmat; Indayani, Lilik (Universitas Muhammadiyah Sidoarjo, 2025)
Background: The increasing smartphone usage in Indonesia has intensified market competition, requiring companies to optimize design, brand image, and product quality to influence purchasing behavior. Specific Background: Oppo, as one of the top smartphone brands, remains competitive despite global market fluctuations. Knowledge Gap: Previous studies provided inconsistent results on how brand image and design shape purchasing decisions. Aims: This study investigates how product design, brand image, and product quality affect purchasing decisions for Oppo smartphones. Results: Using quantitative methods with 96 respondents, findings reveal that product design and quality significantly affect purchase decisions, while brand image does not. Novelty: The study identifies quality as the dominant factor influencing consumer behavior among Indonesian smartphone users. Implications: The results suggest that manufacturers should focus on design innovation and maintain product quality consistency to sustain market competitiveness. Highlights:• Product design and quality significantly influence Oppo smartphone purchase decisions.• Brand image does not significantly affect consumer decision-making.• Quality perception is the key driver for Indonesian consumers. Keywords: Product Design, Brand Image, Product Quality, Purchase Decision, Oppo Smartphone